(untitled) (Annals of Medical Research, 2021)
Aim: The number of diagnostic coronary angiography is increasing. Although previously thought that non-obstructive coronary artery disease (CAD) does not cause an increase in mortality risk, there is recently evidence that it increases mortality. In this study, we aimed to determine the mortality rates and possible predictors of all-cause death in long-term follow-up of patients who underwent coronary angiography (CAG) due to stable angina and whose SYNTAX score was zero including normal coronary arteries, minimal CAD or non-obstructive CAD, coronary slow flow, coronary artery aneurysms and ectasia.Materials and Methods: This study included 1489 patients who underwent CAG due to stable angina pectoris. In-hospital and post-discharge follow-up data were obtained. Patients’ CAG images were evaluated and SYNTAX scores were calculated using the website calculator. Results: Among the 1489 patients, 64 (4.3%) all-cause deaths were observed during the 19 ± 1.1 months of follow up period. Although, no significant difference was observed between the 2 groups in terms of the presence of plaque in coronary arteries with a vessel diameter of ≤ 1.5 mm, the rate of patients with plaque in coronary arteries with a diameter of > 1.5 mm was significantly higher in the group of patients who died compared to the patients living (48 (75%) vs 842 (% 59.1), p = 0.011). The cumulative survival curve of the patients was obtained and in patients with coronary plaque in any of the coronary arteries with a vessel diameter of > 1.5 mm was significantly associated with worse survival.Conclusion: There was increase in all-cause mortality in patients who underwent CAG due to stable angina and who have at least one non-obstructive lesion in the coronary arteries > 1.5 mm. Therefore, appropriate risk classification, life style changes and appropriate medical follow-up may be important in these patients.